Research-Based Learning Models in Physics for 21st Century Students - Estuhono Estuhono (AL-ISHLAH: Jurnal Pendidikan, 2022)
The relevance of the Four Cs skills (critical thinking and problem solving, communication, cooperation, and creativity and invention) in the twenty-first century inspired this study. One of the efforts to achieve this goal is through the application of the Research-Based Learning (RBL) model in high school physics learning. The purpose of this study was to determine the effectiveness of the RBL model to improve students' Four Cs skills. The type of research used is R D using the Plomp development design which is focused on the assessment phase. The data collection instrument for the four Cs skills in this study used an assessment instrument for critical thinking and problem solving, communication, collaboration, creativity, and innovation. This instrument was developed by referring to Preparing 21st Century Students for A Global Society: An Educator's Guide to the “Four Cs”. Data Analysis of Student Four Cs Skills was carried out by measuring the percentage of students' achievement of Four Cs skills by comparing the frequency of skills acquired with the total number of frequencies of students' Four Cs skills. The average percentage of critical thinking and problem-solving skills reached 80, 21%, communication skills reached 82, 17%, collaboration skills reached 82, 11%, and creativity and innovation skills reached 79, 36%. The research-based learning methodology was found to be successful in increasing students' Four Cs skills during the evaluation phase.